Spatial Heterogeneity and Hierarchy of Metropolitan Area Expansion and Land Surface Temperature Evolution: A Twin City Perspective - Mengqiu Cui; Liang Zhou; Wenda Wang; Dongqi Sun; Bo Yuan; Wei Wei (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing, 2024)
Understanding the response of land surface temperature (LST) to urbanization is important for coping with urban warming. However, few studies have discussed the impact of twin-city integration on LST. Here, we explored the relationship between the twin-city integration and LST over the Xi'an-Xianyang Metropolitan Area (XXMA) using the local contour tree algorithm during 2000–2020. Results indicate that: 1) The urban integration of XXMA is obvious, and the spatial scope of XXMA converges toward the Weihe River between the two cities. Besides, its structure tends to be more complex, which develops from 3 levels and 8 centers to 10 levels and 33 centers from 2000 to 2020. 2) The heat islands of XXMA tend to connect and reach the maximum area of 547.43 km2 in 2015, while the LST evolution in two cities is not synchronized. The LST contour tree of Xi'an increased to 6 levels and 26 centers in 2000–2015 and simplified to 5 levels and 17 centers in 2020, while it increased from 1 to 4 levels in Xianyang in 2000–2020. 3) Synergistic effects exist between urban expansion and LST evolution. The correlation coefficient and bivariate Moran's I between nighttime light (NTL) and LST are greater than 0.35, indicating NTL and LST are correlated and have pleasurable spatial consistency. The high–high agglomeration of NTL and LST increases by 132% in area over the 20-year period, showing a trend toward integration. The study results can provide a scientific basis for thermal environment management and urban climate improvement in XXMA.